2003
DOI: 10.1063/1.1562940
|View full text |Cite
|
Sign up to set email alerts
|

On the new vortex shedding mode past a rotating circular cylinder

Abstract: To examine in detail the behavior of a new vortex shedding mode found in a previous investigation ͓Phys. Fluids 14, 3160 ͑2002͔͒, a two-dimensional numerical study on the laminar incompressible flow past a rotating circular cylinder in the Reynolds number range 60рReр200 and at rotational rates 0р␣р6 was carried out. The results obtained clearly confirm the existence of the second shedding mode for the entire Reynolds number range investigated. A complete bifurcation diagram ␣(Re) was compiled defining both ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
46
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 8 publications
7
46
1
Order By: Relevance
“…Coutanceau & Ménard 1985;Badr et al 1990;Kang, Choi & Lee 1999;He et al 2000;Stojković, Breuer & Durst 2002;Mittal & Kumar 2003;Rao et al 2013). Over a small range of α 4 there is a secondary region of wake unsteadiness, comprising low-frequency one-sided vortices, as shown by Mittal & Kumar (2003), Stojković et al (2003) and Pralits, Brandt & Giannetti (2010). Numerical simulations have shown that the critical Reynolds number of the secondary instability associated with the spanwise undulation of the von Kármán vortices increases with Reynolds number (El Akoury et al 2008;Rao et al 2015).…”
mentioning
confidence: 97%
“…Coutanceau & Ménard 1985;Badr et al 1990;Kang, Choi & Lee 1999;He et al 2000;Stojković, Breuer & Durst 2002;Mittal & Kumar 2003;Rao et al 2013). Over a small range of α 4 there is a secondary region of wake unsteadiness, comprising low-frequency one-sided vortices, as shown by Mittal & Kumar (2003), Stojković et al (2003) and Pralits, Brandt & Giannetti (2010). Numerical simulations have shown that the critical Reynolds number of the secondary instability associated with the spanwise undulation of the von Kármán vortices increases with Reynolds number (El Akoury et al 2008;Rao et al 2015).…”
mentioning
confidence: 97%
“…The critical α values are presented in Figure 9 for different Reynolds numbers in comparison with the results of Stojkovic et al (2003) and Mittal & Kumar (2003). This figure shows a stability map with the three curves representing the rotation rates (α L1 ; α L2 and α L3 ) at which three transitions between steady and unsteady flows with the four flow regimes are found: I VS (vortex shedding) regime for α ≤ α L1 , I Steady regime at α L1 < α < α L2 , II VS (vortex shedding) regime for α L2 ≤ α ≤ α L3 and II Steady regime for α > α L3 .…”
Section: Flow Transitionsmentioning
confidence: 99%
“…The correlations proposed by Zukauskas [25] have been widely practiced to compute the average Nusselt number in different ranges of Reynolds number. Saparrow et al [26] proposed a correlation to predict average Nusselt number for a wide range of Reynolds and Prandtl number: …”
Section: Re Prmentioning
confidence: 99%